PENGEMBANGAN MODUL AJAR BERBASIS HOTS PADA MATERI RIAS CIKATRI KELAS XI SMK NEGERI 2 JOMBANG - Elvi Putri Gunawan; Nia Kusstianti; Sri Usodoningtyas; Dindy Sinta Megasari (Jurnal Tata Rias, 2024)
The development of this HOTS-based teaching module is the development of a teaching module which aims to help students get used to thinking critically and creatively in learning activities with the help of HOTS (high level thinking) which is applied in the teaching module to help students get used to thinking critically and creatively in learning activities . Finding out how HOTS-based teaching modules were developed at SMKN 2 Jombang, their viability, student learning results, and student reactions to utilizing them with cikatri makeup material are the goals of the study. R&D (Research and Development) is the sort of research that is used. Overall media feasibility may be classified as "Very Feasible" based on study findings on the viability of learning modules. The average score for the structure of teaching modules is 92%, and the average score for the preparation of teaching modules is 88%. According to research findings, 86.7% of student learning outcomes in the cognitive area were deemed complete. Students might be classified as "Very Eligible" or 81-100% based on the evaluation results of their replies, which were 93.3%. According to these findings, the creation of teaching modules based on HOTS is highly appropriate for use as a learning tool to enhance cognitive learning outcomes and get excellent feedback from students.